2022
DOI: 10.1155/2022/3300903
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Gut Microbiota on the Development of Neurodegenerative Diseases

Abstract: Neurodegenerative disorders are marked by neuronal death over time, causing a variety of cognitive and motor dysfunctions. Protein misfolding, neuroinflammation, and mitochondrial and protein clearance system dysfunction have all been identified as common pathways leading to neurodegeneration in recent decades. An altered microbiome of the gut, which is considered to play a central role in diseases as well as health, has recently been identified as another potential feature seen in neurodegenerative disorders.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…Additionally, the ROT plus UD-ZnO and ROT plus MC-ZnO groups had significantly greater AChE levels than the ROT-treated group. The findings revealed that AChE inhibition in rotenone-exposed organisms and biosynthesized ZnO-NPs contributes to restoring AChE levels, which is consistent with earlier studies [ 85 ].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the ROT plus UD-ZnO and ROT plus MC-ZnO groups had significantly greater AChE levels than the ROT-treated group. The findings revealed that AChE inhibition in rotenone-exposed organisms and biosynthesized ZnO-NPs contributes to restoring AChE levels, which is consistent with earlier studies [ 85 ].…”
Section: Discussionsupporting
confidence: 92%
“…A fundamental cholinergic system enzyme called acetylcholinesterase (AChE) regulates various physiological activities, such as memory and locomotion [ 71 ]. It stops cholinergic neurotransmission between synapses by hydrolyzing acetylcholine into choline and acetate [ 72 , 73 ]. A significant statistical ( p < 0.001) decrease in AChE activity was seen in this study when the larvae were exposed to AgNO 3 for 24 h compared to the control/untreated larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Human neurodegenerative disorders and neurotoxicity have been associated with pyrethroid pesticides, organochlorine insecticides, and organophosphate insecticides. DDT has low toxicity (rat oral LD 50 = 113 mg/kg) ( 93 ). Furthermore, oral administration of 3.5 or 35 mg DDT/day to people for up to 18 months did not result in observable toxicity or neurotoxicity.…”
Section: Relationship Of the Toxicity Of Some Pesticides With Alterat...mentioning
confidence: 99%